Caracterização dos polimorfismos dos genes das interleucinas 1a (ALFA) e 8 na doença de Alzheimer - Vendramini, Alex Augusto (2007)
Alzheimer disease (AD) was described by Alois Alzheimer in 1907. This is a neurodegenerative, progressive and irreversible disorder. It frequently occurs at around 60 years of age it could also have precocious occurrence at 50 years of age.It represents 50% of the cases of dementia in U.S.A. and corresponds to the fourth cause of death of aged in this country. Inflammatory process has been reported in numerous neurodegenerative disorders such as Parkinson s disease, stroke and Alzheimer s disease (AD). In AD, the inflammatory response is mainly located to the vicinity of amyloid plaques. Cytokines, such as Interleukin-1 (IL-1) and Interleukin-8 (IL-8), have been clearly involved in this inflammatory process. The expression of these cytokines is induced by the presence of amyloid-â peptide. These cytokines are also able to promote the accumulation of amyloid-â peptide, leading to injuries in the Nervous Central System (NCS. Polymorphisms from several interleukins have been related with the risk of developing AD. Several studies about isolated genes showed that allele T of the Interleukin-1á (IL-1á) (-889) is an important risk factor for AD but few papers have been directed for the genic interaction between two or more Interleukins. The present study our proposal was genotype the polymorphisms of promoter region of the Interleukin-1á (IL-1á) (-889) and Interleukin-8 (IL-8) (-251), respectively, and to correlate the genotypes of these two genes in the patients and controls. We studied 123 Alzheimer s disease (AD) patients, 76 elderly healthy controls and 95 young healthy controls. In relation to the genotyping of the polymorphisms of these genes and their genic interaction, we did not verified statistical difference among the groups of the individuals studied.